Hubungan riwayat kekurangan energi kronis pada saat kehamilan dengan kejadian stunting pada balita di wilayah kerja puskesmas kalimukti kecamatan Pabedilan kabupaten Cirebon - Juariah, Siti (UKInstitute, 2024)
The consequences that can occur when toddlers experience stunting include short-term and long-term impacts. Short-term impacts on children experiencing stunting include disrupted brain development that can affect intelligence, growth disorders, and metabolic disturbances. The aim of this research is to determine the relationship between a history of chronic energy deficiency during pregnancy and the occurrence of stunting in toddlers in the Kalimukti Community Health Center area, Pabedilan District, Cirebon Regency. This is quantitative research using a pre-experimental research method with a One Group Pretest Posttest approach. The research population includes all mothers with toddlers aged 0-24 months in the Kalimukti Community Health Center area, Pabedilan District, Cirebon Regency in 2023, totaling 256. The sample selection technique uses purposive sampling. Data analysis involves univariate and bivariate analysis. The chi-square test results show a significant relationship between chronic energy deficiency in pregnant women and the occurrence of stunting in toddlers aged 0-24 months (ρ=0.004). Based on the Odds Ratio (OR) calculation, pregnant women with Chronic Energy Deficiency during pregnancy are 15.4 times more likely to experience stunting in their children in the future.